Improving students’ reading comprehension through implementation of content based instruction - Karim, Ahmad Faisal; Nurweni, Ari; Nisa, Khairun (U-Jet Unila Journal of English Language Teaching, 2024)
Reading is the most required skill a student should have as a basis for learning any other language skills. Having reading skill opens up a whole new world of opportunities to learn, not only language but also many other schools of knowledge, as most of modern information is recorded in texts. The purpose of this research as a whole is to find out whether Content Based Instruction significantly improves students’ reading comprehension. The subject of this research was 24 students of class VII RI of SMPIT Permata Bunda Alawiyah. The instrument of the research was multiple choice test. The data were analysed by using Paired Sample T-test with a significant level of p<0.05 through SPSS version 26.0. The findings revealed a significant improvement in students’ reading comprehension after the implementation of Content Based Instruction (CBI),